Peacemap (Peace Education and Character Building through Mindfulness and Action Packed-Play): Educational Media for Alleviating Problems of Student Intolerance - Anggraeni, Leni; Saepudin, Epin; Darmawan, Cecep; Putra, Tarekh Febriana; Irawan, Hendri; Azis, Abdul; Firdaus, Pipin (Journal of Ecohumanism, 2025)
Social transformation influences a growing style of tolerance, so it is necessary to modify peace education programs to support this situation. This research reveals the phenomenon of the development of tolerance in society and its influences on the emergence of a social problem function that is currently active. Studies show that the issue of tolerance is no longer just about inclusivity. But it also involves the issue of tolerance as a personal perception. The initial justification for the problem which became the starting point in the research was the low level of social sensitivity and accommodative attitude of individual people as a basis for acting tolerantly. using the Design and Development (D&D) method. To form an educational medium to eradicate the problem of intolerance among students. Through this method, this research succeeded in offering an educational medium in the form of PEACEMAP (Peace Education and Character Building through Mindfulness and Action Packed-Play). This study will reveal the systematic journey of research in discovering media starting from identification and justification of objects, preparation of media, and its potential utility for alleviating the problem of tolerance.